The Effect of Play-Based Learning on Early Reading and Simple Sentence Writing Skills in First-Grade Students - Sri Muriati; Martono Martono; Imam Ghozali; Antonius Totok Priyadi; Masriani Masriani (Sakura Digital Nusantara, 2026)
This study examines the effect of a play-based learning approach on beginning reading and simple sentence writing skills among first-grade elementary school students. A pre-experimental study employing a one-group pretest–posttest design was conducted with 25 first-grade students selected through total sampling. Data were collected through beginning reading and simple sentence writing tests administered before and after the implementation of the play-based learning approach and analyzed using descriptive statistics and a paired-samples t-test at a significance level of 0.05. The results showed that students’ literacy performance improved significantly after the intervention. The mean score increased from 65.00 in the pretest to 82.00 in the posttest, while the percentage of students achieving mastery learning rose from 32% to 84%. The paired-samples t-test confirmed a statistically significant difference between pretest and posttest scores (t = [insert t-value], p < 0.001), indicating that the play-based learning approach effectively enhanced students’ beginning reading and simple sentence writing skills. These findings suggest that integrating play-based learning into early-grade literacy instruction can create more active, meaningful, and developmentally appropriate learning experiences. This study contributes to the literature by providing empirical evidence on the simultaneous improvement of beginning reading and simple sentence writing skills through a play-based learning approach, offering a more comprehensive perspective on early literacy development in elementary education.